The relationship between physical match performance and 48-h post-game creatine kinase concentrations in English Premier League soccer players. Issue 6 (December 2016) - Scott, A; Malone, JJ; Morgans, R; Burgess, D; Gregson, W; Morton, JP; Drust, B
The aim of the investigation was to determine the relationship between blood creatine kinase and physical match performance in 15 elite male soccer players competing in the English Premier League. Blood samples were collected 48 h following a competitive match and analysed for creatine kinase concentration immediately after collection. Physical match performance data were collected using a computerised tracking system (Prozone®) from >6 matches for each player. Mean ± S.D creatine kinase concentration 48 h post-match was 520 ± 224 µ.mol.l −1 . Large individual variation in creatine kinase response at this time point was observed (184 µ.mol.l −1 to 1573 µ.mol.l −1 ). No significant correlation coefficients were observed between the chosen indicators of physical match performance and creatine kinase concentration 48 h post-match. These data suggest that creatine kinase concentrations are elevated as a consequence of playing a soccer match. Creatine kinase may also be of limited value in supporting important decisions in the coaching process.